Role of leptin in female reproduction - Pérez Pérez, Antonio (2015)
Reproductive function is dependent on energy resources. The role of weight, body composition, fat distribution and the effect of diet have been largely investigated in experimental female animals as well as in women. Any alteration in diet and/or weight may induce abnormalities in timing of sexual maturation and fertility. However, the cellular mechanisms involved in the fine coordination of energy balance and reproduction are largely unknown. The brain and hypothalamic structures receive endocrine and/or metabolic signals providing information on the nutritional status and the degree of fat stores. Adipose tissue acts both as a store of energy and as an active endocrine organ, secreting a large number of biologically important molecules termed adipokines. Adipokines have been shown to be involved in regulation of the reproductive functions. The first adipokine described was leptin. Extensive research over the last 10 years has shown that leptin is not only an adipose tissue-derived messenger of the amount of energy stores to the brain, but also a crucial hormone/cytokine for a number of diverse physiological processes, such as inflammation, angiogenesis, hematopoiesis, immune function, and most importantly, reproduction. Leptin plays an integral role in the normal physiology of the reproductive system with complex interactions at all levels of the hypothalamic-pituitary gonadal (HPG) axis. In addition, leptin is also produced by placenta, where it plays an important autocrine function. Observational studies have demonstrated that states of leptin excess, deficiency, or resistance can be associated with abnormal reproductive function. This review focuses on the leptin action in female reproduction.